Silicosis in finishing workers in quartz conglomerates processing - Guarnieri, Gabriella; Salasnich , Mauro; Lucernoni, Paolo; Sbaraglia, Marta; Putzu, Maria Grazia; Zuliani, Paolo; Rossi, Federica; Vio, Stefania; Bianchi, Leonardo; Martinelli, Andrea; Gottardo, Ottorino; Bizzotto, Rosanna; et al. (La Medicina del Lavoro, 2020)
Introduction. Outbreaks of silicosis have bene recently reported in artificial stone workers. Aim. To describe the features of silicosis in quartz conglomerate workers in North-Eastern Italy. Methods. Active search of pneumoconiosis was performed in 11 companies of North-Eastern Italy involved in the fabrication of quartz conglomerate countertops. Occupational history, lung function tests, chest X-ray and high resolution computed tomography (HRCT) were performed. In selected cases, trans-bronchial biopsies were taken for histological evaluation and identification of silica crystals in the tissue. Cumulative exposure to crystalline silica was estimated. Results. We recruited 45 workers and 24 cases of silicosis were diagnosed. Mean age at diagnosis was 43 years and duration of exposure to quartz conglomerate dust was 3.5 to 20 years. The average silica cumulative exposure was 4.3 mg/m3/y. Abnormal findings were detected in 42% of chest X-rays, in 33% of spirometry and 50% of carbon monoxide lung diffusion (DLco). HRCTs were abnormal in all cases showing well-defined rounded opacities, irregular/linear intralobular opacities and bilateral enlarged mediastinal lymph-nodes. Histological findings consistent with silicosis were observed in 24 cases. Numerous silica particles (diameter 0.1-5 µm) were identified in lung tissue. Conclusions.We reported an unexpected high incidence of silicosis in Italian workers exposed to quartz conglomerate dust. The results suggest that chest HRCT is indicated for screening of workers with high exposure to silica and DLco should be added to spirometry in health surveillance. More rigorous application of safety regulations and more effective preventive interventions at work are necessary.